Identification of sequence motifs for the protein components of type IX secretion system - Reeki Emrizal,; Nor Azlan Nor Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Porphyromonas gingivalis is the bacterium responsible for chronic periodontitis, a severe periodontal disease. Virulence factors produced by this bacterium are secreted by the Type IX Secretion System (T9SS). The specific functions for each protein component of the T9SS have yet to be characterized thus limiting our understanding of the mechanisms associated with the translocation and modification processes of the T9SS. This study aims to identify the sequence motifs for each T9SS component and predict the functions associated with each discovered motif using motif comparisons. We extracted the sequences of 20 T9SS components from the P. gingivalis proteome that were experimentally identified to be important for T9SS function and used them for homology searching against fully sequenced bacterial proteomes. We developed a rigorous pipeline for the identification of seed sequences for each protein family of T9SS components. We verified that each selected seed sequence are true members of the protein family hence sharing conserved sequence motifs using profile Hidden Markov Models. The motifs for each T9SS component are identified and compared to motifs in the Pfam database. The discovered motifs for 11 components with known functions matched the motifs associated with the reported functions. We also suggested the putative functions for four components. PorM and PorW might form the putative energy transduction complex. PorP and PorT might be the putative O-deacylases. The identified motifs for five components matched the motifs associated with functions that related/unrelated to the T9SS.